Induced Growth and Nutrient Uptake in Dalbergia sissoo by Arbuscular Mycorrhizae and Chemical Fertilizers - Paroha, Seema; Subrahmanyam, D.; Shukla, P. K. (Indian Journal of Agroforestry, 2020)
Effect of AM in combination with chemical fertilizer on growth and nutrient uptake on Dalbergia sissoo was studied Of all the different combinations the treatment comprising of high dose of AM V1Â (500 spores) with low dose of NPK; proved to be the best combination for all the observed parameters. The results revealed that plant growth, nutrient accumulation and nodule formation of D. sissoo were significantly improved by using mycorrhizal inoculation in presence of low levels of NPK3 (120 kg N, 30 Kg P2O5 and 75 kg K/ha). The AM conferred maximum benefit to tree seedlings in nutrient deficient with low input for sustainable forestry condition.